Method for directly preparing nanocellulose-based carbon fiber loaded Fenton oxidation reaction catalyst by high-temperature hydrothermal one-pot method

The nanocellulose-based carbon fiber-loaded Fenton oxidation reaction catalyst was prepared by high-temperature water-heating one-pot method, which solved the sludge problem and catalyst recovery problem of Fenton's method when treating organic pollutants under acidic conditions, and achieved efficient and stable degradation of organic pollutants.

CN119701954APending Publication Date: 2025-03-28SHANGHAI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510019904.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

When the existing Fenton method treats organic pollutants under acidic conditions, it is necessary to have acidic conditions and subsequent neutralization process to easily produce iron-containing sludge, and the use of dissolved Fe2+ has difficulties in recycling.

Method used

The nanocellulose-based carbon fiber-based one-pot method is used to directly prepare the Fenton oxidation reaction catalyst, and the nanocellulose-based carbon fibers are used as a support, and metal oxides are formed on the nanocarbon fibers by hydrothermal conditions.

Benefits of technology

It achieves efficient oxidation and degradation of organic pollutants under neutral conditions, solves the problems of catalyst agglomeration and recovery, and improves the specific surface area and activity of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701954A_ABST
    Figure CN119701954A_ABST
Patent Text Reader

Abstract

The invention discloses a method for directly preparing a nanocellulose-based carbon fiber loaded Fenton oxidation reaction catalyst through a high-temperature hydrothermal one-pot method, and relates to the technical field of Fenton oxidation catalysis. The preparation method comprises the following steps: adding soluble ferric salt or transition metal salt into a nanocellulose aqueous solution, adding alkali while stirring at 30-60 DEG C to react to generate hydroxide, and forming uniform turbid liquid; and then reacting in a hydrothermal autoclave at 180-300 DEG C for 6-24 hours, carbonizing the nano cellulose into nano carbon fibers, and decomposing the metal hydroxide to form metal oxide which is loaded on the nano carbon fibers. According to the method for directly preparing the nano-cellulose-based carbon fiber loaded Fenton oxidation reaction catalyst through the high-temperature hydrothermal one-pot method, the preparation technological process is simple, raw materials are easy to obtain, the preparation process is clean and free of pollution, and the obtained product is easy to recycle after organic pollutants are subjected to Fenton oxidation degradation; the method has a wide application prospect in the field of harmless treatment of organic pollutants.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of Fenton oxidation catalysis, and in particular to a method for directly preparing a nano-cellulose-based carbon fiber-loaded Fenton oxidation reaction catalyst by a high-temperature hydrothermal one-pot method. Background Art

[0002] Chemical oxidation is a fast and efficient method for treating organic pollutants. Among them, the Fenton method uses Fe 2+ and H2O2, can effectively oxidize and degrade organic pollutants in water. This method has a simple treatment process and mild reaction conditions. However, the Fenton method requires acidic conditions to react. After the reaction is completed, Fe 2+ It is easy to produce iron-containing sludge.

[0003] In order to avoid the direct use of dissolved Fe 2+ In recent years, ion-loaded or doped solid catalysts have been developed to replace dissolved Fe 2+ After use, the solid catalyst can be reused through a simple solid-liquid separation process, which has become the main trend of current research and development of Fenton reaction catalysts.

[0004] Cellulose is a renewable resource, and nanocellulose prepared from it is a cellulose material with a size between 1 and 100 nanometers in one dimension. It has the advantages of hydrophilicity, biodegradability, biocompatibility, and excellent mechanical properties. Nanocellulose chains are rich in hydroxyl groups, which enables them to form nanocellulose solutions with good dispersibility and high suspension stability after being dispersed in water. Using nanocellulose-based carbon fibers as catalyst carriers can not only solve the problem of catalyst agglomeration, but also obtain metal oxide nanoparticles with high specific surface area and high activity, while also effectively solving the problem of catalyst recovery. Summary of the invention

[0005] The present invention provides a method for directly preparing a nanocellulose-based carbon fiber-loaded Fenton oxidation reaction catalyst by a high-temperature hydrothermal one-pot method. The nanocellulose-based carbon fiber is used as a catalyst carrier, which not only solves the problem of catalyst agglomeration and realizes the preparation of metal oxide nanoparticles with high specific surface area and high activity, but also effectively solves the problem of catalyst recovery.

[0006] To achieve the above object, the present invention provides a method for directly preparing a nanocellulose-based carbon fiber-supported Fenton oxidation reaction catalyst by a high-temperature hydrothermal one-pot method, comprising the following steps: S1. Diluting the nanocellulose aqueous solution with a solid content of 3% to a nanocellulose aqueous solution with a solid content of 1.5%-2% using deionized water; S2, adding a soluble iron salt and / or a soluble transition metal salt to the nanocellulose aqueous solution having a solid content of 1.5%-2%, and stirring to form a uniform solution; S3, slowly add a soluble base to the uniform solution of step S2, adjust the system pH to 8.5-9.5, continue stirring the reaction for 1-2 hours, and obtain a uniform suspension; S4, placing the uniform suspension obtained in step S3 into a hydrothermal reaction kettle for hydrothermal reaction at 180-300° C. for 6-24 hours; S5. After the reaction is completed, the hydrothermal reactor is cooled to room temperature and then opened to pour out the product. The product is filtered, washed, dried, lightly ground, and sieved to obtain a nanocellulose-based carbon fiber-supported Fenton oxidation reaction catalyst.

[0007] Preferably, in step S2, the soluble iron salt includes ferric nitrate or ferric chloride.

[0008] Preferably, in step S2, the soluble transition metal salt includes copper sulfate, copper nitrate, copper chloride, cobalt nitrate, cobalt chloride, manganese chloride or manganese nitrate.

[0009] Preferably, in step S2, the mass of the added soluble iron salt or soluble transition metal salt is 5-20% of the mass of the nanocellulose aqueous solution with a solid content of 3%.

[0010] Preferably, in step S3, the soluble alkali includes aqueous ammonia, sodium carbonate, sodium hydroxide, potassium carbonate or potassium hydroxide.

[0011] Preferably, in step S3, the temperature of the uniform solution is maintained at 30°C-60°C while adding the soluble base.

[0012] The method of the present invention directly preparing a nanocellulose-based carbon fiber-loaded Fenton oxidation reaction catalyst by a high-temperature hydrothermal one-pot method has the following beneficial effects: (1) A soluble base reacts with a metal salt to form a metal hydroxide, which forms a uniform suspension in the nanocellulose dispersion. During the high-temperature hydrothermal process of the suspension, the nanocellulose is hydrothermally carbonized to form nanocarbon fibers, and the metal hydroxide is decomposed under the high-temperature hydrothermal effect to form a metal oxide loaded on the nanocarbon fibers, thereby obtaining a nanocellulose-based carbon fiber-loaded Fenton oxidation reaction catalyst. (2) The production process is short and the operating conditions are simple. The nanocarbon fiber-loaded composite metal catalyst is prepared by one-pot hydrothermal preparation, and the production cost is low. (3) Since the metal is evenly loaded on the nanocarbon fibers, it is easy to recover. In addition, due to the large specific surface area of ​​the prepared catalyst, it has a high catalytic activity.

[0013] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is a SEM image of the Fenton oxidation reaction catalyst supported by nanocellulose-based carbon fibers prepared in Example 1; Figure 2 This is a diagram showing the catalytic degradation of phenol by the Fenton oxidation reaction catalyst supported by the nanocellulose-based carbon fiber prepared in Example 1. DETAILED DESCRIPTION

[0015] In order to make the purpose, technical scheme and advantages disclosed in the embodiments of the present invention more clearly understood, the embodiments of the present invention are further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the embodiments of the present invention and are not intended to limit the embodiments of the present invention. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0016] Embodiment 1 A method for directly preparing a nanocellulose-based carbon fiber-supported Fenton oxidation reaction catalyst by a high-temperature hydrothermal one-pot method comprises the following steps: (1) Weigh 100 g of a nanocellulose aqueous solution with a solid content of 3% (purchased from Zhejiang Chuanhua Chemical Group), put it into a beaker, and dilute it with deionized water to obtain a nanocellulose aqueous solution with a solid content of 2%.

[0017] (2) Weigh 10 g of ferric chloride and 2 g of cupric chloride and add them to a 2% solid content nanocellulose aqueous solution, and stir to form a uniform solution.

[0018] (3) Heat the uniform solution of step (2) to maintain its temperature at 45°C, and slowly add 25% by weight ammonia water while stirring until the pH of the system reaches 9. Stop adding ammonia water and continue stirring the reaction for 2 hours to obtain a uniform suspension.

[0019] (4) The uniform suspension obtained in step (3) is placed in a hydrothermal reaction vessel and subjected to a hydrothermal reaction at 210° C. for 12 h.

[0020] (5) After the reaction is completed, the hydrothermal autoclave is cooled to room temperature, the hydrothermal autoclave is opened, the product is poured out, filtered, washed, dried at 120°C for 10 h, lightly ground, and sieved to obtain a 50-mesh nanocellulose-based carbon fiber-supported Fenton oxidation reaction catalyst.

[0021] Embodiment 2 A method for directly preparing a nanocellulose-based carbon fiber-supported Fenton oxidation reaction catalyst by a high-temperature hydrothermal one-pot method comprises the following steps: (1) Weigh 100 g of a nanocellulose aqueous solution with a solid content of 3%, put it into a beaker, and dilute it with deionized water to obtain a nanocellulose aqueous solution with a solid content of 1.5%.

[0022] (2) Weigh 15 g of ferric chloride and 2 g of cupric chloride and add them to a nanocellulose aqueous solution with a solid content of 1.5%, and stir to form a uniform solution.

[0023] (3) Heat the uniform solution of step (2) to keep its temperature at 50°C. Slowly add solid NaOH while stirring until the pH of the system reaches 9. Stop adding and continue stirring the reaction for 1 hour to obtain a uniform suspension.

[0024] (4) The uniform suspension obtained in step (3) is placed in a hydrothermal reaction vessel and subjected to a hydrothermal reaction at 230° C. for 10 h.

[0025] (5) After the reaction is completed, the hydrothermal autoclave is cooled to room temperature, the hydrothermal autoclave is opened, the product is poured out, filtered, washed, dried at 120°C for 10 h, lightly ground, and sieved to obtain a 50-mesh nanocellulose-based carbon fiber-supported Fenton oxidation reaction catalyst.

[0026] Embodiment 3 A method for directly preparing a nanocellulose-based carbon fiber-supported Fenton oxidation reaction catalyst by a high-temperature hydrothermal one-pot method comprises the following steps: (1) Weigh 100 g of a nanocellulose aqueous solution with a solid content of 3%, put it into a beaker, and dilute it with deionized water to obtain a nanocellulose aqueous solution with a solid content of 1.5%.

[0027] (2) Weigh 18 g of ferric chloride and add it to a nanocellulose aqueous solution with a solid content of 1.5%, and stir to form a uniform solution.

[0028] (3) Heat the uniform solution of step (2) to maintain its temperature at 55°C. Slowly add anhydrous sodium carbonate solid while stirring until the pH of the system reaches 8.5. Stop adding and continue stirring the reaction for 1.5 hours to obtain a uniform suspension.

[0029] (4) The uniform suspension obtained in step (3) was placed in a hydrothermal reaction vessel and subjected to hydrothermal reaction at 200° C. for 15 h.

[0030] (5) After the reaction is completed, the hydrothermal autoclave is cooled to room temperature, the hydrothermal autoclave is opened, the product is poured out, filtered, washed, dried at 120°C for 10 h, lightly ground, and sieved to obtain a 50-mesh nanocellulose-based carbon fiber-supported Fenton oxidation reaction catalyst.

[0031] Embodiment 4 A method for directly preparing a nanocellulose-based carbon fiber-supported Fenton oxidation reaction catalyst by a high-temperature hydrothermal one-pot method comprises the following steps: (1) Weigh 100 g of a nanocellulose aqueous solution with a solid content of 3%, put it into a beaker, and dilute it with deionized water to obtain a nanocellulose aqueous solution with a solid content of 2%.

[0032] (2) Weigh 12 g of ferric chloride and 2 g of cobalt chloride, add them to a nanocellulose aqueous solution with a solid content of 2%, and stir to form a uniform solution.

[0033] (3) Heat the uniform solution of step (2) to keep its temperature at 50°C, and slowly add anhydrous sodium carbonate solid while stirring until the pH of the system reaches 9, then stop adding, and continue stirring the reaction for 1 hour to obtain a uniform suspension.

[0034] (4) The uniform suspension obtained in step (3) is placed in a hydrothermal reaction vessel and subjected to a hydrothermal reaction at 240° C. for 10 h.

[0035] (5) After the reaction is completed, the hydrothermal autoclave is cooled to room temperature, the hydrothermal autoclave is opened, the product is poured out, filtered, washed, dried at 120°C for 10 h, lightly ground, and sieved to obtain a 50-mesh nanocellulose-based carbon fiber-supported Fenton oxidation reaction catalyst.

[0036] Embodiment 5 A method for directly preparing a nanocellulose-based carbon fiber-supported Fenton oxidation reaction catalyst by a high-temperature hydrothermal one-pot method comprises the following steps: (1) Weigh 100 g of a nanocellulose aqueous solution with a solid content of 3%, put it into a beaker, and dilute it with deionized water to obtain a nanocellulose aqueous solution with a solid content of 2%.

[0037] (2) Weigh 8 g of ferric chloride and 4 g of cupric chloride, add them to a 2% solid content nanocellulose aqueous solution, and stir to form a uniform solution.

[0038] (3) Heat the uniform solution of step (2) to keep its temperature at 60°C. Slowly add anhydrous sodium carbonate solid while stirring until the pH of the system reaches 9. Stop adding and continue stirring the reaction for 1 hour to obtain a uniform suspension.

[0039] (4) The uniform suspension obtained in step (3) is placed in a hydrothermal reaction vessel and subjected to a hydrothermal reaction at 260° C. for 8 h.

[0040] (5) After the reaction is completed, the hydrothermal autoclave is cooled to room temperature, the hydrothermal autoclave is opened, the product is poured out, filtered, washed, dried at 120°C for 10 h, lightly ground, and sieved to obtain a 50-mesh nanocellulose-based carbon fiber-supported Fenton oxidation reaction catalyst.

[0041] Test Example 1 like Figure 1 Shown is a SEM image of the Fenton oxidation reaction catalyst supported by nanocellulose-based carbon fibers prepared in Example 1.

[0042] From the SEM image, we can see that the carbonized cellulose is a relatively large fibrous particle, and the loaded composite metal oxide particles are very small, and are evenly distributed on the carbon fiber at the nanoscale, which indicates that the prepared catalyst has a good morphology.

[0043] Test Example 2 Phenol degradation experiment: Take 200 mL of phenol / H2O2 mixed solution (phenol 200 mg / L, H2O2 0.15 wt%), and adjust the pH to 3 with 1 mol / L NaOH and 1 mol / L HNO3 solution. Then add 0.5 g / L of the catalyst obtained in Example 1 to the solution, and react at 45°C for 3 h. After the reaction, take 5 mL of the reaction solution and put it into an ice water bath to quickly cool down to terminate the reaction, centrifuge it at 4000 r / min for 10 min to separate the catalyst and the solution, and take the supernatant after centrifugation for analysis.

[0044] like Figure 2 As shown, it is a diagram of the catalytic degradation of phenol by the Fenton oxidation reaction catalyst supported by the nanocellulose-based carbon fiber prepared in Example 1, where C0 is the initial concentration of the phenol solution, and C is the concentration of the phenol solution corresponding to different times t.

[0045] Under this condition, the removal rate of phenol in 200 mg / L phenol simulated wastewater can reach 98.12% after 3 hours of reaction, which is close to 100%.

[0046] After the degradation experiment is completed, the catalyst is separated by centrifugation at 4000r / min, then washed with deionized water, and dried at 120°C for 10h before being used in the next experiment.

[0047] The nanocellulose-based carbon fiber-supported Fenton oxidation reaction catalyst prepared in Example 1 was recycled, and the results of the cycle test are shown in Table 1 below: Table 1

[0048] It can be concluded from Table 1 that after being reused four times, the activity of the catalyst is still relatively high, reaching more than 90% after four uses, and has good stability and recycling performance.

[0049] Therefore, the present invention provides a method for directly preparing a nano-cellulose-based carbon fiber-loaded Fenton oxidation reaction catalyst by a high-temperature hydrothermal one-pot method, wherein a soluble base reacts with a metal salt to generate a metal hydroxide, and the metal hydroxide forms a uniform suspension in a nano-cellulose dispersion; during the high-temperature hydrothermal process of the suspension, the nano-cellulose is hydrothermally carbonized to form nano-carbon fibers, and the metal hydroxide is decomposed under the high-temperature hydrothermal action to form a metal oxide loaded on the nano-carbon fibers, thereby obtaining a nano-cellulose-based carbon fiber-loaded Fenton oxidation reaction catalyst; the preparation process of the present invention is simple, the raw materials are easily available, the preparation process is clean and pollution-free, and the obtained product can be easily recycled and reused after Fenton oxidation degrades organic pollutants, and the method has broad application prospects in the field of harmless treatment of organic pollutants.

[0050] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for directly preparing a nanocellulose-based carbon fiber-supported Fenton oxidation reaction catalyst by a high-temperature hydrothermal one-pot method, characterized in that: The steps include: S1. Diluting the nanocellulose aqueous solution with a solid content of 3% to a nanocellulose aqueous solution with a solid content of 1.5%-2% using deionized water; S2, adding a soluble iron salt and / or a soluble transition metal salt to the nanocellulose aqueous solution having a solid content of 1.5%-2%, and stirring to form a uniform solution; S3, slowly add a soluble base to the uniform solution of step S2, adjust the system pH to 8.5-9.5, continue stirring the reaction for 1-2 hours, and obtain a uniform suspension; S4, placing the uniform suspension obtained in step S3 into a hydrothermal reaction kettle for hydrothermal reaction at 180-300° C. for 6-24 hours; S5. After the reaction is completed, the hydrothermal reactor is cooled to room temperature and then opened to pour out the product. The product is filtered, washed, dried, lightly ground, and sieved to obtain a nanocellulose-based carbon fiber-supported Fenton oxidation reaction catalyst.

2. The method for directly preparing nanocellulose-based carbon fiber-supported Fenton oxidation reaction catalyst by a high-temperature hydrothermal one-pot method according to claim 1, characterized in that: In step S2, the soluble iron salt includes ferric nitrate or ferric chloride.

3. The method for directly preparing nanocellulose-based carbon fiber-supported Fenton oxidation reaction catalyst by a high-temperature hydrothermal one-pot method according to claim 1, characterized in that: In step S2, the soluble transition metal salt includes copper sulfate, copper nitrate, copper chloride, cobalt nitrate, cobalt chloride, manganese chloride or manganese nitrate.

4. The method for directly preparing nanocellulose-based carbon fiber-supported Fenton oxidation reaction catalyst by a high-temperature hydrothermal one-pot method according to claim 1, characterized in that: In step S2, the mass of the added soluble iron salt or soluble transition metal salt is 5-20% of the mass of the nanocellulose aqueous solution with a solid content of 3%.

5. The method for directly preparing nanocellulose-based carbon fiber-supported Fenton oxidation reaction catalyst by a high-temperature hydrothermal one-pot method according to claim 1, characterized in that: In step S3, the soluble alkali includes aqueous ammonia, sodium carbonate, sodium hydroxide, potassium carbonate or potassium hydroxide.

6. The method for directly preparing nanocellulose-based carbon fiber-supported Fenton oxidation reaction catalyst by a high-temperature hydrothermal one-pot process according to claim 1, characterized in that: In step S3, the temperature of the uniform solution is maintained at 30°C-60°C while adding the soluble base.